Bleomycin-induced interstitial pneumonia in dogs. Issue 6 (November 1971) - Fleischman, Robert W.; Baker, John R.; Thompson, George R.; Schaeppi, Ulrich H.; Illievski, Vladimir R.; Cooney, David A.; Davis, Ruth D.
Abstract : The intravenous administration of Bleomycin to 10 dogs at different dosages resulted in varying degrees of interstitial pneumonia in all cases and a lower incidence of nephrosis, foot pad excoriation and ulceration, onychoptosis, and alopecia. Pulmonary changes did not occur as a simple dose-related phenomenon. The lesions required at least 38 days to become apparent and appeared to increase in severity with time. Even at the lowest dose used (0·625 mg/kg body weight) very severe changes were seen 128 days after cessation of therapy. Morphological features of interstitial pneumonia were subpleural localization, focal mesothelial hyperplasia, marked hyperplasia and metaplasia of type II pneumocytes, fetalization of alveoli, and a pleomorphic inflammatory infiltrate. In cross-sections of lung lobes selected for histology approximately 1 to 22% of the parenchyma contained lesions. Involved areas showed marked elastosis, excess of reticular fibres, fibrosis, and increased acid mucopolysaccharides. The administration of Bleomycin produced pulmonary changes similar in many respects to those reported in busulphan-treated patients and desquamative interstitial pneumonia. The finding of interstitial pneumonia and pulmonary fibrosis in dogs treated with low doses over prolonged periods points the need to monitor pulmonary function in humans treated with Bleomycin.